The Application of Encaustic Technique in the Creation of LIMBOSIS Figurative Sculpture Artworks - Kholisoh, Siti Nur; Supriatna, Supriatna; Racmadi, Gustiyan (LPPM Institut Seni Indonesia Padangpanjang, 2024)
This study explores the use of the encaustic technique in creating sculpture art themed around the quarter-life crisis. The encaustic technique, which involves the application of hot wax on figures made of wire and polyurethane, was chosen for its flexibility and ability to create rich textures and visual dimensions. This research aims to investigate how the encaustic technique can capture and convey the emotional and psychological complexities experienced by individuals in the age range of 20–30 years, often referred to as the quarter-life crisis phase. The artwork titled LIMBOSIS was created using the encaustic technique through an experimental approach involving wax, polyurethane, wire, and digital elements. The results demonstrate that the encaustic technique is effective in expressing complex emotional nuances and provides aesthetic depth to art installations. Traditionally used in painting, this technique has been successfully adapted to contemporary sculpture. These findings make a significant contribution to the development of contemporary art, particularly in the context of creating works that explore psychological and social issues